KAJIAN HADIS DILIHAT DARI TEKS DAN KONTEKS - Idris Siregar (UIN Sumatera Utara Medan, 2022)
In understanding a good hadith, there are many scientific disciplines and methods that can be used, one of which is the study of hadith with accurate theory and methodology. So that textual and contextual approaches in Hadith studies also function in understanding the hadith discussed. With a textual and contextual approach, we know that a hadith does not appear suddenly, but because there are causes for it. The textual approach is more likely to apply to mahdah (pure) worship between human relations and God (hablumminallah) such as prayer for example. While the contextual approach looks more at the historical, sociological, cultural and temporal context of a hadith so that in understanding the hadith it is not so standard but it is wiser by studying the contemporary conditions of today's society without eliminating the spirit of the hadith text. Textual and Contextual approaches are very meaningful in the scientific understanding of Hadith